The Distribution of Purchasing Power in Pakistan, 1985-86 (The Pakistan Development Review, 1989)
Suppose that you and I earn the average income of Pakistan and that we are looking at a parade in which the whole population of Pakistan takes part. It is a spectacular parade because the size of all marchers is proportionate to their income. We have the average height. Anyone who earns more than the average is taller than we are; anyone who earns less than the average is smaller. The procession is organized in such a way that the smallest walks in front and the tallest in the rear. The parade moves at uniform speed and its dUration is one hour exactly. What do we see? What is the size of the marchers in front and in the rear? Who passes by during the first ten minutes, the second ten minutes, etc.? Where do they live, in which pr